Preparação dos eletrodos óxidos cerâmicos para aplicação em filmes finos do tipo Pb1-xCaxTiO3 - Zampieri, Marcelo (Universidade Federal de São Carlos, 2008)
In this work the compounds LaNiO3 (LNO) and La0,5Sr0,5CoO3-δ (LSCO) were synthesized for application as oxide electrodes in thin films and the compound Pb1-xCaxTiO3 (PCT10) was synthesized as a material with a ferroelectric property. These compounds were synthesized by the Polymeric Precursor Method. This method makes the synthesis in aqueous medium possible, in the open air, using easily available reagents. The thin films were deposited for spin coating on substrates of Pt/Ti/SiO2/Si. The thermic treatment temperature for the crystallization was of 700°C for 2 h, using Air and Oxygen atmospheres, separately. The structural and morphological characterization of the films presents a transition from tetragonal phase to pseudocubic in accordance with the base electrode used. Electrical measurements for the PCT10 film crystallized in Air, showed dielectric constant of 166 for PCT10 deposited on Pt, 189 for PCT10 deposited on LNO and 112 for PCT10 deposited on LSCO. And the values of dielectric loss, measured at 100 kHz frequency, were 0,018, 0,023 and 0,189, respectively. For films annealed in Oxygen atmosphere these values were 627 for PCT10 on PT, 503 on LNO and 534 on LSCO. And the values of dielectric loss were 0,031, 0,089 and 0,122, respectively. Values of remaining polarization (2Pr) for films annealed in Air were of 11,38 μC/cm2 for PCT10 on Pt, 7,69 for PCT10 on LNO and 11,35 for PCT10 on LSCO and coercive field (Ec) 257,18, 187,11 and 217,18 kV/cm, respectively. The fatigue measurements presented a high degradation for films annealed in Air after 108 cycles and a very good performance for films annealed in O2 with emphasis on film of PCT10 deposited on LNO wich did not show fatigue after 108 cycles of polarization. These results suggest the viability of the oxide electrodes for ferroelectric films.
Preparation of ceramic oxide electrodes for application in thin films of Pb1-xCaxTiO3
Keywords: Físico-química; Método químico; Eletrodos de óxidos; Ferroelétricos; CIENCIAS EXATAS E DA TERRA::QUIMICA